Comparison of Efficacy and Safety Between Laparoscopic and Open Radical Resection for Hilar Cholangiocarcinoma—A Propensity Score-Matching Analysis - He, Yong-Gang; Huang, Wen; Ren, Qian; Li, Jing; Yang, Feng-Xia; Deng, Chang-Lin; Li, Li-Qi; Peng, Xue-Hui; Tang, Yi-Chen; Zheng, Lu; Huang, Xiao-Bing; Li, Yu-Ming (Frontiers in Oncology, 2022)
Abstract BACKGROUND Successful laparoscopic radical resection of HCCA(IIIA, IIIB） requires excellent surgical skills and rich experience. Furthermore, the safety and effectiveness of this operation are still controversial. AIM To retrospectively analyze and compare the efficacy and safety of laparoscopic and open surgery for patients with HCCA. METHODS Clinical imaging and postoperative pathological data of 89 patients diagnosed with HCCA (IIIA, IIIB） and undergoing radical resection in our center from January 2018 to March 2022 were retrospectively analyzed. Among them, 6 patients (4 were lost to follow-up and 2 were pathologically confirmed to have other diseases after surgery) were ruled out, and clinical data was collected from the remaining 83 patients for statistical analysis. After 1:2 propensity score matching (PSM), 32 and 16 patients respectively in the open surgery group and laparoscopic surgery group were remained. The demographic data, Bismuth type, perioperative data, intraoperative data, postoperative complications, pathological findings, and long-term survivals were compared between these two groups. RESULTS After 1:2 PSM, 32 patients in the open surgery group and 16 patients in the laparoscopic surgery group were included for further analysis. Baseline characteristics and pathological outcomes were comparable between the two groups. Statistically significant differences between the two groups were observed in intraoperative blood loss and operative time, as it were 400-800 mL vs 200-400 mL (P=0.012) and (407.97±76.06) min vs (489.69±79.17) min (P=0.001) in the open surgery group and laparoscopic surgery group, respectively. The R0 resection rate of the open group was 28 cases ( 87.5 % ), and the R0 resection rate of the laparoscopic group was 15 cases ( 93.75 % ). The two groups showed no significant difference in terms of surgical approach, intraoperative blood transfusion, incidence of postoperative complications, and short- and long-term efficacy (P>0.05). CONCLUSIONS Laparoscopic radical resection of HCCA has comparable perioperative safety compared to open surgery group, as it has less bleeding and shorter operation time. Although it is a promising procedure with the improvement of surgical skills and further accumulation of experience, further investigations are warranted before its wider application.